2017
DOI: 10.5897/ajpp2016.4695
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological, pharmaceutical, cosmetic and diagnostic applications of sulfated polysaccharides from marine algae and bacteria

Abstract: Marine environment with rich biodiversity offer unlimited choice for novel biopolymers. Sulfated polysaccharides isolated from marine algae and bacteria constitute an important group in the marinederived biomolecules and biopolymers. They possess unique structural features which can be exploited to their fullest potential in the development of new therapeutic molecules, design of nanocarriers and stimuli-responsive drug delivery systems, development of anti-aging and moisturizing creams and as molecular probes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Another characteristic feature is the glycosidic linkage, which has a crucial effect on the bioactivity of polysaccharides irrespective of other physicochemical properties. In a study by Sutapa et al, the positive effect of α (1 → 6) glycosidic linkages on the scavenging reactions of EPS was also suggested because such linkages can provide flexible regions and increase the accessibility of the reactive groups for its interaction with the free radicals. Likewise, in the present investigation, the NMR studies revealed α and β anomeric sugars and α (1 → 6) glycosidic linkages, which confirmed their prominent role in the antioxidative activity of EPS-b.…”
Section: Resultsmentioning
confidence: 99%
“…Another characteristic feature is the glycosidic linkage, which has a crucial effect on the bioactivity of polysaccharides irrespective of other physicochemical properties. In a study by Sutapa et al, the positive effect of α (1 → 6) glycosidic linkages on the scavenging reactions of EPS was also suggested because such linkages can provide flexible regions and increase the accessibility of the reactive groups for its interaction with the free radicals. Likewise, in the present investigation, the NMR studies revealed α and β anomeric sugars and α (1 → 6) glycosidic linkages, which confirmed their prominent role in the antioxidative activity of EPS-b.…”
Section: Resultsmentioning
confidence: 99%
“…Marine oligosaccharides generally have antioxidation activity and anti-inflammatory activity, especially algal-sulfated oligosaccharides. , Moreover, these activities appear to correlate with the sulfate content of oligosaccharides. In recent years, oligoporphyrans, oligocarrageenan, oligoulvan, and oligofucoidan have been continuously confirmed to have obvious activities. There are some reports that sulfated oligosaccharides with these activities are bound to play an important role in the future of the cosmetic industry . Oligosaccharides with potent antioxidant activity can be used as fibroblast proliferation activators in aesthetic treatments, such as anti-wrinkle treatments, natural anti-photoaging compounds, and the prevention of skin aging. , Non-sulfate oligosaccharides present in laminarin have also been reported to stimulate the regeneration of human fibroblasts and keratinocytes…”
Section: Application Of Bioactive Oligosaccharidesmentioning
confidence: 99%
“…In addition to being strong anticoagulants, antithrombotics, and fibrinolytics, PSs are also able to exhibit other effects that are useful in the treatment of viral infections, accounting for known data on their antiviral activity [116][117][118][119], anti-inflammatory activity, and ability to reduce the proinflammatory cytokine production and other beneficial effects [17,56,[120][121][122][123][124]. Such a wide range of biological activity is due to the chemical nature of PSs.…”
Section: Treatment Strategies Of Covid-19-induced Hypercoagulation and The Potency Of Seaweed Sulfated Pss For The Correction Of Hemostasmentioning
confidence: 99%